181k views
1 vote
20) Simplify: 3ab(4b-ab) + 5b2(a2 + 2)

2 Answers

4 votes

Answer:


12ab^2+2a^2b^2+10b^2

Explanation:


3ab(4b-ab) + 5b^2(a^2 + 2)\\\\\mathrm{Expand}\:3ab\left(4b-ab\right):\quad 12ab^2-3a^2b^2\\\\=12ab^2-3a^2b^2+5b^2\left(a^2+2\right)\\\\\mathrm{Expand}\:5b^2\left(a^2+2\right):\quad 5a^2b^2+10b^2\\\\=12ab^2-3a^2b^2+5a^2b^2+10b^2\\\\\mathrm{Add\:similar\:elements:}\:-3a^2b^2+5a^2b^2=2a^2b^2\\\\=12ab^2+2a^2b^2+10b^2

User Roman Rdgz
by
5.2k points
4 votes
2a^2 b^2 + 12ab^2 + 10b^2
User Emre Akcan
by
5.1k points